Thermo-economic assessment of a gas microturbine-absorption chiller trigeneration system under different compressor inlet air temperatures (2019)
This manuscript presents a thermo-economic analysis for a trigeneration system integrated by an absorption refrigeration chiller, a gas microturbine, and the heat recovery steam generation subsystem. The effect of the compressor inlet air temperature on the thermo-economic performance of the trigeneration system was studied and analyzed in detail based on a validated model. Then, we determined the critical operating conditions for which the trigeneration system presents the greatest exergy destruction, producing an increase in the costs associated with loss of exergy, relative costs, and operation and maintenance costs. The results also show that the combustion chamber of the gas microturbine is the component with the greatest exergy destruction (29.24%), followed by the generator of the absorption refrigeration chiller (26.25%). In addition, the compressor inlet air temperature increases from 305.15 K to 315.15 K, causing a decrease in the relative cost difference of the evaporator (21.63%). Likewise, the exergo-economic factor in the heat exchanger and generator presented an increase of 6.53% and 2.84%, respectively.